The Effect of Biology Online Learning Based on Edmodo Group WhatsApp on Learning Outcomes Based on the Learning Motivation of Students - Eldyana Rahayu Putri; Moralita Chatri; Syamsurizal Syamsurizal; Irdawati Irdawati (Postgraduate, University of Mataram, 2021)
COVID-19 pandemic has changed the order of people's lives, including the education sector. The transition from conventional learning to online learning often encounters obstacles, including determining the appropriate type of online learning media. One solution that can be used is to use learning media in the form of WhatsApp assisted by Edmodo in online learning. This study aims to determine the effect of using online learning media in the form of WhatsApp assisted by Edmodo in improving learning outcomes in terms of students' learning motivation. The experimental technique used was a 2x2 factorial design. The study population was all students of class X SMA Negeri 1 Bukittinggi. Sampling was done by using the purposive proportional sampling technique. The learning outcome instrument is a written test, and the learning motivation instrument is a questionnaire, the data analysis technique used two-way ANOVA test and Bonferroni advanced test. The results showed that the average value of learning outcomes in the control class was 79.38 lower than the experimental class, with an average value of 83.50. Significant differences were also obtained in the group of students with high learning motivation, with an average of 94.00 in experimental and 86.00 in the control classes. Different results were obtained in the group of students with low learning motivation, which had an average of 73.00 in the experimental class and 72.75 in the control class. The learning outcomes obtained are influenced by the interaction of choosing the type of media online learning with students' learning motivation